An introduction to the theory of formal languages and automata - Levelt, W. J. M. (Willem J. M.), 1938- (John Benjamins Pub., 2008)
The present text is a re-edition of Volume I of Formal Grammars in Linguistics and Psycholinguistics, a three-volume work published in 1974. This volume is an entirely self-contained introduction to the theory of formal grammars and automata, which hasn't lost any of its relevance. Of course, major new developments have seen the light since this introduction was first published, but it still provides the indispensible basic notions from which later work proceeded. The author's reasons for writing this text are still relevant: an introduction that does not suppose an acquaintance with sophistic.